On certain features of atmospheric circulations in periods of droughts (MAUSAM, 1982)
An attempt to identify the main features of atmospheric circulation accompanying drought formation was made based on the analysis of data describing droughts occurred in the Northern Hemisphere in the period from 1970 to 1980. Conditions of circulation in the troposphere of the Northern Hemisphere in 1972 were considered for this purpose. In that year the drought spread over  vast territories of Africa, North India and East Europe. The total annual precipitation in that period on the territory between Sahara and 15 deg. N was less than half the long-range annual normal precipitation. The deficit of rainfall in Niger, Mali in June, July and August amounted to 35-40 per cent of relevant monthly- means. Delay of the beginning of monsoon in June 1972 and its long interruption in July resulted in drought occurrence in many regions of North India. In summer mean air temperatures over the European USSR were 4.6 deg. above normal. Conditions of atmospheric circulation in 1972, particularly in summer months, were significantly different from normal. Unusually intensive and blocking situations were observed in the above mentioned territories both in summer and in winter during extended periods; mean pressure was considerably above normal. Tropical troposphere in June 1972 according to "TROPEX-72" data was characterized by considerable anomalies, namely, the subtropical jet stream was at the latitude of winter climatic planetary maximum of wind, trade jet streams were shifted by 10 degrees towards the equator, as compared  with their climatic location.